2019
DOI: 10.1055/s-0039-1691820
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Fossa Arteriovenous Malformations: Experience with 14 Patients and a Systematic Review of the Literature

Abstract: Background The optimal management of posterior fossa arteriovenous malformations (pfAVMs) is a matter of debate. To advance this discussion, we present our clinical series and the results of a systematic literature review according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Methods Fourteen consecutive patients with pfAVMs were admitted between 2007 and 2018. Preoperative status, radiologic parameters, and outcome were assessed. A systematic literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In contrast, in the ruptured AVMs subgroup only 62% of the patients had a similar outcome. Other authors reported that hemorrhagic presentation is associated with less favorable postoperative outcome, although the condition of patients can improve over time [ 2 , 3 , 13 ]. Lawton et al also stress the fact that patients with ruptured AVMs have a worse clinical presentation, which can mask the outcome, and therefore, the risk of neurological worsening associated with unruptured AVMs following surgical resection should not be underestimated [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the ruptured AVMs subgroup only 62% of the patients had a similar outcome. Other authors reported that hemorrhagic presentation is associated with less favorable postoperative outcome, although the condition of patients can improve over time [ 2 , 3 , 13 ]. Lawton et al also stress the fact that patients with ruptured AVMs have a worse clinical presentation, which can mask the outcome, and therefore, the risk of neurological worsening associated with unruptured AVMs following surgical resection should not be underestimated [ 13 ].…”
Section: Discussionmentioning
confidence: 99%